Hubungan Kekuatan Otot Tungkai Terhadap Kemampuan Shooting Siswa Ekstrakurikuler SMAN 1 Porehu - Ical Ical; Taslim Taslim; Irsan Kahar; Syamsul Darmawan; Rachmat Hidayat (Universitas Hamzanwadi, 2026)
The problem addressed in this study is the low shooting ability of students in the soccer extracurricular program at SMAN 1 Porehu, as evidenced by inaccurate ball direction and slow ball speed, which is suspected to be caused by weak lower-body muscle strength. This study aims to determine the relationship between lower-body muscle strength and shooting ability among these students. The method used was a quantitative study with a correlational approach. The sample consisted of 15 students selected through purposive sampling. The testing instruments included a vertical jump test to measure lower-body muscle strength and an observation sheet to assess shooting ability. Data analysis techniques utilized simple correlation and regression tests with the aid of SPSS. The results indicate a significant relationship between lower-body muscle strength and shooting ability, with a coefficient of determination of 67.1%. This means that lower limb muscle strength contributes 67.1% to shooting ability, while the remainder is influenced by other factors. The conclusion of this study is that the better the students’ lower limb muscle strength, the higher their shooting ability. Therefore, lower limb muscle strengthening exercises need to be integrated into extracurricular programs.